2021
DOI: 10.1186/s12883-021-02372-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of white matter lesions on the prognosis of acute cardioembolic stroke without reperfusion therapy

Abstract: Background Few studies have investigated the influence of white matter lesions (WMLs) on the prognosis of acute cardioembolic stroke (CES). We aimed to explore the role of WMLs in predicting 3-month prognosis of CES without reperfusion therapy. Methods A number of 251 acute CES patients without reperfusion therapy at a single center were retrospectively recruited. The severity of WMLs was evaluated by Fazekas scale and patients were divided into mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“… 18 , 19 Our previous study enrolled CES patients identified by cranial CT or MRI scan and found that WMLs are an independent risk factor for the outcome. 20 In this study, patients were evaluated by MRI and it was found that WMH was an independent risk factor for poor prognosis, which was consistent with the results of studies focusing on ischemic stroke with other causes. 21 …”
Section: Discussionsupporting
confidence: 88%
“… 18 , 19 Our previous study enrolled CES patients identified by cranial CT or MRI scan and found that WMLs are an independent risk factor for the outcome. 20 In this study, patients were evaluated by MRI and it was found that WMH was an independent risk factor for poor prognosis, which was consistent with the results of studies focusing on ischemic stroke with other causes. 21 …”
Section: Discussionsupporting
confidence: 88%
“…A total Fazekas score, ranging from 0 to 6, was estimated by summing the Fazekas scores for PWMH and DWMH. We defined severe WMH as a total Fazekas score of ≥3, as previously described (Guo et al, 2021). In accordance with the STRIVE criteria (Staals et al, 2014;Duering et al, 2023), the SVD score was determined by a double-blinded review of FLAIR images by two expert vascular neurologists (M Lee and S-H Lee; ICC = 0.92, p < 0.001).…”
Section: Data Collection and Definition Of Parametersmentioning
confidence: 99%
“…A total Fazekas score, ranging from 0 to 6, was calculated by summing the periventricular and subcortical WMLs scores [24]. According to previous studies, severe WMLs were defined as a total Fazekas score ≥ 3 [25][26][27].…”
Section: Image Acquisition and Analysismentioning
confidence: 99%